2018
DOI: 10.1038/s41598-018-24967-y
|View full text |Cite|
|
Sign up to set email alerts
|

Whole exome sequencing reveals rare variants linked to congenital pouch colon

Abstract: We demonstrate the application of whole exome sequencing to discover the rare variants for congenital pouch colon, acronymed CPC. For 18 affected individuals in a total of 64 samples, we sequenced coding regions to a mean coverage of 100×. A sufficient depth of ca. 94% of targeted exomes was achieved. Filtering against the public SNP/variant repositories, we identified a host of candidate genes, EPB41L4A and CTC1 associated with colon, neural/brain muscles and Dyskeratosis Congenita maladies. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…Since 2005, several efforts have been made to understand the clinical genetic makeup of CPC, but no attempt has been made to study the genes responsible for the disease. Recently, we have screened 64 subjects out of which 18 affected samples were analysed using whole exome sequencing (WES) [ 3 ]. Identifying mutations and variants in both coding and non-coding regions affecting such phenotypes are not only of valuable interest towards clinical applications but are also important for enormous prognostic value for therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2005, several efforts have been made to understand the clinical genetic makeup of CPC, but no attempt has been made to study the genes responsible for the disease. Recently, we have screened 64 subjects out of which 18 affected samples were analysed using whole exome sequencing (WES) [ 3 ]. Identifying mutations and variants in both coding and non-coding regions affecting such phenotypes are not only of valuable interest towards clinical applications but are also important for enormous prognostic value for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As the lncRNAs play a role in regulation [ 18 ], there is an enormous scope for ascertaining lncRNA-protein interactions. In this study, we inferred a lncRNA, viz.lnc-EPB41-1-1promiscuously interacting with six protein-coding genes and established its interaction with KIF13A, a 202 kDa trafficking protein [ 19 ] and a bona fide gene causal to CPC [ 3 ]. Furthermore, this kinesin family of microtubule-based motor proteins is known to regulate various processes such as mannose-6-phosphate receptor (M6PR) transport besides mediating melanosome biogenesis and cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…312) It was found by WES that EPB41L4A has genetic susceptibility to colon, nerve/brain muscle and congenital keratosis. (20) To understand the role of EPB41L4A in cancer, studies have explored the role of EPB41L4A in cell lines. This study found that when β-catenin was depleted in SW480 cells, the RNA expression of EPB41L4A was significantly reduced (SW480 cells are colorectal cancer cell lines).…”
Section: Discussionmentioning
confidence: 99%
“…(19) Only a few studies have shown that EPB41L4A has genetic susceptibility to colon, nerve/brain muscle and congenital keratosis. (20) However, there is currently no clinical prognostic study on the EPB41L4A gene in any types of cancer. The study integrates multiple data from MM to achieve three goals.…”
Section: Ivyspringmentioning
confidence: 99%
“…respectively (Mathur et al, 2018). In a separate study, we have also inferred the role of long non-coding RNAs (lncRNAs) from a WES and identified lnc-EPB41-1-1, located in the intergenic regions of EPB41 that is known to be interacting with KIF13A (Gupta et al, 2018).…”
mentioning
confidence: 99%